Earning Per Share, Return on Asset Serta Dampaknya atas Tobin's Q di Perusahaan Sektor Industri Manufaktur Tahun 2017 - Verliani Dasmaran; Tri Yulaeli (Jurnal Buana Akuntansi, 2020)
This study aims to determine the effect of Earning Per Share and Return On Assets in sectors of manufacturing companies in the period 2017. This study is classified as a causative study. The research sample was determined using the purposive sampling method to obtain 37 sample companies. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is a moderated regression analysis (MRA). Based on the research results shows that EPS and ROA variables together have a significant effect on Tobin, s Q. Adjust R Square value of 0.590 so it can be interpreted that the magnitude of the contribution of Earning Per Share and Return On Asset variables to Tobin's Q in 2017 manufacturing companies in various industries is 59% while the remaining 41% is determined by several other factors beyond the Earning Per Share and Return On Asset variables.